Rate-limiting steps in the dark-to-light transition of Photosystem II - revealed by chlorophyll-a fluorescence induction - Melinda Magyar (Nature Portfolio, 2018)
Abstract Photosystem II (PSII) catalyses the photoinduced oxygen evolution and, by producing reducing equivalents drives, in concert with PSI, the conversion of carbon dioxide to sugars. Our knowledge about the architecture of the reaction centre (RC) complex and the mechanisms of charge separation and stabilisation is well advanced. However, our understanding of the processes associated with the functioning of RC is incomplete: the photochemical activity of PSII is routinely monitored by chlorophyll-a fluorescence induction but the presently available data are not free of controversy. In this work, we examined the nature of gradual fluorescence rise of PSII elicited by trains of single-turnover saturating flashes (STSFs) in the presence of a PSII inhibitor, permitting only one stable charge separation. We show that a substantial part of the fluorescence rise originates from light-induced processes that occur after the stabilisation of charge separation, induced by the first STSF; the temperature-dependent relaxation characteristics suggest the involvement of conformational changes in the additional rise. In experiments using double flashes with variable waiting times (∆τ) between them, we found that no rise could be induced with zero or short ∆τ, the value of which depended on the temperature - revealing a previously unknown rate-limiting step in PSII.